2020
DOI: 10.1016/j.apnr.2020.151283
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs of symptom management and associated factors among the HIV-positive population in Shanghai, China: A cross-sectional study

Abstract: Background: People living with HIV/AIDS (PLWHA) are a vulnerable group who experience multiple physiological and psychological symptoms. A better understanding of unmet symptom management needs will allow researchers to design interventions that are more reflective of deficits in care and more effective at improving patient care. Few studies have focused on unmet needs for symptom management in PLWHA particularly in China. Factors influencing Chinese PLWHA symptom management needs are rarely discussed. Aim: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
1
11
0
1
Order By: Relevance
“…e l s e v i e r . c o m / l o c a t e / i j i d and found that the number of years since the diagnosis of HIV was not associated with overall symptom severity (Dong et al, 2020). Zhu et al conducted a multicenter, cross-sectional study among 1116 PLWH in China and found that a longer HIV-positive duration was not associated with more severe symptoms (Zhu et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…e l s e v i e r . c o m / l o c a t e / i j i d and found that the number of years since the diagnosis of HIV was not associated with overall symptom severity (Dong et al, 2020). Zhu et al conducted a multicenter, cross-sectional study among 1116 PLWH in China and found that a longer HIV-positive duration was not associated with more severe symptoms (Zhu et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Bringsvor et al (2018) discovered that COPD patients diagnosed with high symptom burden had poorer self-management. Dong et al (2020) found that symptom burden reduced selfmanagement behaviours in a population of HIV-positive patients.…”
Section: Discussionmentioning
confidence: 98%
“…These results indicated that clinical practitioners should pay attention to helping PLWH improve negative moods. Previous studies indicated that PLWH showed a huge unmet need for emotional support (56,57). Timely and effective regulation of negative moods may be more efficient in helping regulate other mental health symptom dimensions, such as cognitive process symptoms and social adaptation symptoms.…”
Section: Discussionmentioning
confidence: 99%